A skills-matching perspective on talent management: developing strategic agility - Jooss, Stefan; Collings, David G.; McMackin, John; Dickmann, Michael (Wiley, 2024)
Despite two decades of evolution as an area of research and practice, talent management faces ongoing criticism for being overly static in its approach, offering little in terms of enabling strategic agility. This is problematic as organizations increasingly rely on strategic agility to manage their dynamic business operations. Drawing on matching theory and adopting an agility lens, we explore the link between talent management and strategic agility. Through a qualitative research design, encompassing 34 interviews in 15 organizations, we explicate a skills-matching perspective on talent management, including initial and dynamic skills-matching in external and internal labor markets. Through this process, organizations can build a set of dynamic capabilities, underlying two meta-capabilities, strategic sensitivity and resource fluidity, which enable strategic agility. In doing so, we portray skills-matching as an illustration of a processual view on talent management and create a model of developing strategic agility through skills-matching, responsive to external and internal demands.
Keywords: dynamic capabilities; matching theory; skills; strategic agility; talent management